Organic Unity in T. S. Eliot’s The Waste Land (Revue El-Wahat pour les Recherches et les Etudes, 2016)
This paper evinces the organic form in T. S. Eliot’s The Waste Land. Though the poem is always considered as fragmented, it constitutes a unified whole. The poem consummates a marriage between form and content. Eliot’s poetic form resonates with modern existence that is fragmented. His personal experience also has a direct bearing on his style and mode of composition. The form is in tune with the reality of the poet’s psychological crisis and the outside shattered reality. Keywords –  Fragmentation, The Waste Land, T. S. Eliot,  Organic form, Psychological crisis, Unity.